Sosialisasi Dan Pelatihan Aplikasi FIGMA Untuk Siswa SMK YADIKA 5 Dalam Meningkatkan Keterampilan UI/UX - Gilang Herdiansyah; Alfarisi Gymnastiar; Ashapan Husnan; Satria Maulana; Tedi Harun (PT Jurnal Cendekia Indonesia, 2025)
As an effort to improve students' abilities in user interface and user experience (UI/UX) design, a community service activity (PKM) with the theme